How Greece's Systemic Weaknesses Limited the Effectiveness of the Adjustment Programmes - Angelos Kotios; George Galanos; Manolis Koutoulakis (Intereconomics, 2017)
This paper examines the main systemic weaknesses of the Greek economy – structural, institutional and political – and assesses whether they were taken effectively into account in the design and implementation of the three adjustment programmes. We conclude that the economic policy mix that has been implemented through the memorandums focused mainly on treating the symptoms of the crisis instead of decisively dealing with its deeper causes.
Keywords: 330